2000
DOI: 10.2165/00003088-200038010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Consequences and Clinical Relevance of Cytochrome P450 3A4 Inhibition

Abstract: Drug interactions occur when the efficacy or toxicity of a medication is changed by administration of another substance. Pharmacokinetic interactions often occur as a result of a change in drug metabolism. Cytochrome P450 (CYP) 3A4 oxidises a broad spectrum of drugs by a number of metabolic processes. The location of CYP3A4 in the small bowel and liver permits an effect on both presystemic and systemic drug disposition. Some interactions with CYP3A4 inhibitors may also involve inhibition of P-glycoprotein. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
506
2
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 804 publications
(520 citation statements)
references
References 140 publications
2
506
2
10
Order By: Relevance
“…This is an important finding, as CYP3A4 is involved in the metabolism of many drugs, and inhibition or induction of this enzyme can result in clinically important drug interactions. 22,23 The results of this definitive clinical study, which demonstrated no significant pharmacokinetic interactions of dapoxetine with either sildenafil or tadalafil, are in agreement with what is known about the metabolic pathways for dapoxetine and in vitro CYP inhibition and induction profiles for sildenafil and tadalafil. Dapoxetine is extensively metabolized to numerous phase I and phase II metabolites by multiple enzymes, including CYP3A4 and CYP2D6, and in vitro inhibition and induction studies have shown that dapoxetine is a very weak inhibitor of CYP3A4 (unpublished data).…”
Section: Dapoxetine Does Not Interact With Pde-5 Inhibitorssupporting
confidence: 84%
“…This is an important finding, as CYP3A4 is involved in the metabolism of many drugs, and inhibition or induction of this enzyme can result in clinically important drug interactions. 22,23 The results of this definitive clinical study, which demonstrated no significant pharmacokinetic interactions of dapoxetine with either sildenafil or tadalafil, are in agreement with what is known about the metabolic pathways for dapoxetine and in vitro CYP inhibition and induction profiles for sildenafil and tadalafil. Dapoxetine is extensively metabolized to numerous phase I and phase II metabolites by multiple enzymes, including CYP3A4 and CYP2D6, and in vitro inhibition and induction studies have shown that dapoxetine is a very weak inhibitor of CYP3A4 (unpublished data).…”
Section: Dapoxetine Does Not Interact With Pde-5 Inhibitorssupporting
confidence: 84%
“…Because CYP3A4 is the most abundant CYP isozyme in humans and the pathway responsible for metabolism of numerous xenobiotics (Shimada et al, 1994;Li et al, 1995;Dresser et al, 2000), the potential for drug interaction exists. Using in vitro liver microsome systems, ketoconazole, a potent inhibitor of CYP3A4, decreased the formation of temsirolimus metabolites to 10 -20% of control levels (IC 50 o2 mM) (Cai et al, 2007).…”
mentioning
confidence: 99%
“…This assumption is supported by several studies which show that some herbal medicinal products have the capacity to influence plasma levels of drugs (10,11), giving rise to clinical problems of unexpected toxicities and under-treatment seen in different groups of patients. Factors relating to co-administered drugs (dose, dosing regimen, administration route, pharmacokinetic and therapeutic range), herbs (species, dose, dosing regimen, and administration route) and patients (genetic polymorphism, age, gender and pathological conditions) largely determine the extent and thus the clinical relevance of drug interactions with herbs (12). In general terms, the appearance of enhanced drug effects and/or adverse effects is usually associated with a doubling or more in drug plasma concentration (13).…”
Section: Selected Clinically Relevant Botanical-drug Interactionsmentioning
confidence: 99%